Observation of Marfes in the Wendelstein 7-X stellarator with inboard limiters. (11th July 2018) - Wenzel, U.; Biedermann, C.; Kocsis, G.; Szepesi, T.; Blackwell, B.D.; Klose, S.; Knauer, J.; Krychowiak, M.; Stephey, L.; Schmitz, O.; Harris, J.; König, R.; et al.
Abstract: In the first operational campaign of the Wendelstein 7-X (W7-X) stellarator we observed Marfe-like radiation belts at the plasma edge. We describe and analyze the behaviour of these radiation belts, especially with respect to the high density inside the belt, with a set of suitable diagnostics. We present evidence suggesting that these Marfe-like radiation belts are triggered by a drop of the edge temperature below 30 eV. From this observation we draw the conclusion that the physical cause of Marfes in tokamaks and Marfe-like radiation belts in W7-X is the same, namely radiative condensation. Furthermore, both exhibit the device symmetry, i.e. axisymmetry in a tokamak and the fivefold stellarator symmetry in W7-X.